Gendered lives communication, gender, and culture - Wood, Julia T. (Wadsworth Cengage Learning, 2013)
This edition introduces students to theories, research, and pragmatic information, demonstrating the multiple and often interactive ways that our views of masculinity and femininity are shaped within contemporary culture. With the most up-to-date research, balanced perspectives of masculinity and femininity, a personal introduction to the field, and a conversational first-person writing style, this engaging text encourages students to think critically about gender and our society.